(3ZjK GdehGgH GdYdjI TQM GdMce GdYWGFjIs - (3GHf YHGO, eMeO Hf EHQGgje Hf YHO Gddg, J(B792(3g`s ((3eMeO Hf Ydj GdeGdcjs)
(3ChdgG (B:s
(3bGd GdTjN GdEeGeCHh YHO Gddg eMeO Hf EHQGgje Hf YHGO GdfaQj GdQfOj dWa Gddg Hg(B: (3GdMeO ddg GdefaQO HGdYXeI hGdLdGd GdeJhMO HGSJMbGb fYhJ GdceGd GdefRg Yf GdTQcGA hGdfXQGAs
(3BNQgG (B:s
(3hGdhUhd Edi GdeHJZi GdCLdi Hef TQafG Hg Yf Jhdj cd LMhO hcahQ hCNQLfG Ydi jOg ef GdXdeGJ Edi GdfhQ SjOfG hehdGfG eMeO NGJe GdfHjjf hEeGe GdeQSdjf hMHjH QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 299s
(3eYLe GdeDdajf(B: 3 / 34s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs